"The Association of Obesity, Excessive Salt Intake, and Physical Activity with the Incidence of Hypertension at Penanae Community Health Center." - Zuarda Jumainap Rumjani; Darmin Darmin; Muammar Iksan; Juraidin Juraidin (Syifa'Medika, 2026)
Hypertension is a noncommunicable disease that poses a public health problem because it increases the risk of cardiovascular disease, stroke, and kidney failure. Obesity, excessive salt intake, and physical activity are factors believed to be associated with the incidence of hypertension. This study aimed to determine the association between obesity, excessive salt intake, and physical activity with the incidence of hypertension at the Penanae Community Health Center. An analytical observational study with a cross-sectional design was conducted at the Penanae Community Health Center from May to June 2026 among 106 respondents selected using purposive sampling. Respondents were patients aged ?15 years, including pregnant women, who visited the center during the study period and were able to communicate effectively. Blood pressure was measured using a sphygmomanometer by health workers; obesity was determined based on body mass index (BMI); excessive salt intake was assessed using the Semi-Quantitative Food Frequency Questionnaire (SQFFQ); and physical activity was measured using the International Physical Activity Questionnaire (IPAQ). Data analysis was performed using the chi-square test and multiple logistic regression. The results showed no association between obesity (p=0.182) or high salt intake (p=0.370) and hypertension. Physical activity was significantly associated with hypertension (p=0.021) and was the dominant factor based on multivariate analysis (OR=4.118; 95% CI=1.237–13.705). Physical activity is a factor associated with the incidence of hypertension; therefore, increasing physical activity is necessary as a measure to prevent and control hypertension.